Citron Kinase Deficiency Leads to Chromosomal Instability and TP53-Sensitive Microcephaly - Federico Tommaso Bianchi; Chiara Tocco; Gianmarco Pallavicini; Yifan Liu; Fiammetta Vernì; Chiara Merigliano; Silvia Bonaccorsi; Nadia El-Assawy; Lorenzo Priano; Marta Gai; Gaia Elena Berto; Alessandra Maria Adelaide Chiotto; et al. (Cell Reports, 2017)
Mutations in citron (CIT), leading to loss or inactivation of the citron kinase protein (CITK), cause primary microcephaly in humans and rodents, associated with cytokinesis failure and apoptosis in neural progenitors. We show that CITK loss induces DNA damage accumulation and chromosomal instability in both mammals and Drosophila. CITK-deficient cells display “spontaneous” DNA damage, increased sensitivity to ionizing radiation, and defective recovery from radiation-induced DNA lesions. In CITK-deficient cells, DNA double-strand breaks increase independently of cytokinesis failure. Recruitment of RAD51 to DNA damage foci is compromised by CITK loss, and CITK physically interacts with RAD51, suggesting an involvement of CITK in homologous recombination. Consistent with this scenario, in doubly CitK and Trp53 mutant mice, neural progenitor cell death is dramatically reduced; moreover, clinical and neuroanatomical phenotypes are remarkably improved. Our results underscore a crucial role of CIT in the maintenance of genomic integrity during brain development.